Process for the preparation of pectin-ellagic acid covalent complex, product and use

CN122979381APending Publication Date: 2026-10-27KUNMING UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610826977.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-09
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

上述现有技术中采用的有机溶剂体系对于鞣花酸的溶解能力和分散性能远远不足,若将CN202410123968中的有机溶剂直接用于鞣花酸的接枝,鞣花酸在有机相中大量沉淀析出,无法有效参与脂肪酶催化反应,导致接枝效率极低甚至反应失败

Benefits of technology

其一、本发明通过构建特定体积比的水包油型微乳分散体系并结合分步酶促接枝策略,将难溶性鞣花酸以纳米级液滴高度分散于果胶水相中,同时为脂肪酶提供了巨大的油-水界面以激活其界面催化活性,从而解决了充分溶解底物与保持酶活的矛盾,且无需高浓度有机溶剂,反应条件温和,接枝效率高,工艺绿色安全;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979381A_ABST
    Figure CN122979381A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a pectin-quercetin covalent complex, and belongs to the technical field of natural polymer modification and biological catalytic synthesis. In view of the technical problem that quercetin is difficult to be effectively grafted on pectin by an enzyme method due to poor solubility and large steric hindrance, the preparation method comprises the following steps: dissolving pectin in a phosphate buffer solution; dissolving quercetin in dimethyl sulfoxide first, and then adding tetrahydrofuran, and the volume ratio of the two is 1:3-1:5; under high-speed shearing, the organic phase is added into the water phase, and oil-in-water microemulsion is formed by shearing; aspergillus oryzae lipase is added twice, and stirring reaction is carried out at 50 DEG C and pH 7.2+ / -0.1 for 30-40 hours while maintaining pH stability; after reaction, the organic solvent is removed, and through centrifugation, alcohol precipitation, washing, redissolving, dialysis and freeze-drying, the pectin-quercetin covalent complex is obtained, and the mass ratio of pectin, quercetin and lipase is 2-10:1-5:0.3. The complex is used for preparing stable oil-in-water emulsions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of natural polymer modification and biocatalytic synthesis technology. More specifically, this invention relates to a method for preparing a pectin-ellagic acid covalent complex, the product thereof, and its application. Background Technology

[0002] Pectin is a natural anionic polysaccharide widely found in plant cell walls. Due to its excellent thickening, gelling, and emulsifying properties, it has broad application prospects in the food, pharmaceutical, and cosmetic fields. Although natural pectin is soluble in water and polar solvents, its hydrophilic structure results in low surface activity and limited adsorption capacity at the oil-water interface. Especially when used in functional emulsions or for active ingredient delivery, natural pectin exhibits low emulsifying activity and poor emulsion stability, making it difficult to quickly reduce interfacial tension and causing the resulting emulsion to be susceptible to environmental factors (such as pH, ionic strength, and temperature), leading to aggregation or layering. To expand the application of pectin in functional emulsions and active ingredient delivery systems, in recent years, the scientific and industrial communities have widely adopted the approach of introducing hydrophobic functional groups such as polyphenols and fatty acids into the pectin backbone through covalent or non-covalent methods to construct polymer copolymers with amphiphilic structures, thereby improving its adsorption, spreading, and rearrangement capabilities at the oil-water interface.

[0003] Numerous patents and academic publications have reported technical solutions for grafting polyphenols such as phenolic acids and flavonoids onto pectin molecules via esterification or free radical-mediated methods. For example, Chinese patent application CN202410123968 (application number: 202410123968) discloses a pectin graft copolymer and its preparation method. This method involves graft copolymerization of pectin and flavonoids (including naringin dihydrochalcone and hesperidin) under lipase catalysis to prepare a flavonoid-enriched pectin graft copolymer. The organic solvent used includes one or more of tetrahydrofuran and dimethyl sulfoxide. The grafting reaction temperature is 45–55°C, the reaction time is 20–28 h, and the mass ratio of pectin to flavonoids is 1:(0.4–0.8). The resulting product combines the emulsifying properties of pectin with the antioxidant activity of flavonoids. Furthermore, CN114716579B discloses a method for grafting and modifying pectin using coumaric acid, achieving grafting through a redox system. CN113072662A reports a scheme for preparing ferulic acid-beet pectin graft copolymer using laccase as a catalyst.

[0004] While the aforementioned patents provide a useful technical approach for the hydrophobic modification of pectin, the grafted polyphenol monomers are all phenolic acids (ferulic acid, coumaric acid) or flavonoids with specific structures (naringin dihydrochalcone, hesperidin) that are highly soluble in conventional organic solvents. For ellagic acid, the above technical solutions have significant limitations in practical application. Ellagic acid (molecular formula C...) 14H6O8 (formed by the dimerization and lactone formation of gallic acid) is a polyphenolic diester with a highly planar conjugated structure. Its molecule contains multiple phenolic hydroxyl groups and fused aromatic rings, forming a strong intermolecular hydrogen bond network. It is almost insoluble in water, alcohols, tetrahydrofuran, and most organic solvents, slightly soluble in pyridine and alkaline solutions, and only achieves good solubility in dimethyl sulfoxide. The organic solvent systems used in the aforementioned prior art are far from sufficient for the dissolution and dispersion of ellagic acid. If the organic solvents in CN202410123968 are directly used for ellagic acid grafting, a large amount of ellagic acid will precipitate out in the organic phase, failing to effectively participate in the lipase-catalyzed reaction, resulting in extremely low grafting efficiency or even reaction failure.

[0005] Meanwhile, the planar fused-ring π-system of ellagic acid molecules possesses a large spatial volume and steric rigidity. When it approaches the carboxyl or methyl ester reaction sites on the pectin polymer chain under lipase catalysis, it generates a significant steric hindrance effect, drastically reducing the esterification rate and grafting efficiency. The reaction systems in the aforementioned existing technologies mostly involve conventional stirring and mixing, without specifically designing micro-interfaces to address the steric hindrance problem of large-volume polyphenol substrates. Therefore, how to construct a reaction system that can efficiently dissolve ellagic acid while maintaining lipase catalytic activity, and effectively overcome the steric hindrance caused by the large-volume steric structure of ellagic acid molecules, is a key technical challenge that urgently needs to be solved in this field. Summary of the Invention

[0006] One object of the present invention is to solve at least the above-mentioned problems and to provide at least the advantages that will be described later.

[0007] Another objective of this invention is to provide a method for preparing a pectin-ellagic acid covalent complex. This method achieves high dispersion of poorly soluble ellagic acid in the aqueous pectin phase and directional interfacial catalysis of lipases by constructing an oil-in-water microemulsion dispersion system and employing a stepwise enzymatic grafting strategy. This avoids damage to enzyme activity from organic solvents and significantly improves grafting efficiency. The obtained product exhibits excellent emulsifying and antioxidant activity, and the process is green and safe. The emulsifying activity index (EAI) of the prepared pectin-ellagic acid covalent complex is ≥19.1 m. 2 / g, with an emulsification stability index (ESI) ≥ 110 min, significantly enhanced antioxidant properties, achieving a synergistic effect of pectin hydrophobic modification and polyphenol antioxidant enhancement.

[0008] To achieve these objectives and other advantages according to the present invention, a method for preparing a pectin-ellagic acid covalent complex is provided, comprising: S1. Constructing the aqueous phase: Dissolve pectin in phosphate buffer to obtain a pectin solution; S2. Constructing the organic phase: Ellagic acid is dissolved in dimethyl sulfoxide, sonicated until completely dissolved, and then tetrahydrofuran is added to obtain an organic solution of ellagic acid. The volume ratio of dimethyl sulfoxide to tetrahydrofuran is 1:3 to 1:5. S3. Preparation of microemulsion system: Under high-speed shearing conditions of 8000~10000rpm, the ellagic acid organic solution of step S2 is slowly added to the pectin solution of step S1, and the high-speed shearing is carried out for 40~50s to form an oil-in-water microemulsion dispersion. S4. Stepwise enzymatic grafting: Lipase with an activity of 300,000 U / g derived from Aspergillus oryzae was added to the microemulsion dispersion of step S3 in two portions. The mixture was stirred and reacted at 50°C and pH 7.2±0.1 for 30-40 hours. During the reaction, the pH value was measured at regular intervals and alkali solution was added dropwise to maintain pH stability. S5. After the reaction in step S4 is completed, remove the organic solvent, centrifuge to remove insoluble matter, and precipitate the supernatant with alcohol, wash with different concentrations of ethanol alternately, resolubilize, dialyze and freeze dry to obtain the pectin-ellagic acid covalent complex. The mass ratio of pectin, ellagic acid and lipase is 2~10:1~5:0.3.

[0009] Preferably, in step S3, 0.5-2% of hydrophobic modified silica nanoparticles by weight of pectin are added to the reaction system of ellagic acid organic solution and pectin solution before high-speed shearing.

[0010] Preferably, during the stirring reaction in step S4, stirring is paused every 6 to 10 hours, and then sheared at a high speed of 8000 to 10000 rpm for 10 to 20 seconds before stirring continues.

[0011] Preferably, the pectin is apple pectin or citrus pectin.

[0012] Preferably, in step S1, the pH value of the phosphate buffer solution is 7.2-7.8, and the concentration of the pectin solution is 4-20 mg / mL; in step S2, the concentration of ellagic acid in the mixed organic solvent of dimethyl sulfoxide and tetrahydrofuran is 2-10 mg / mL.

[0013] Preferably, in step S4, the lipase is added in two equal amounts, with an interval of 6 to 15 hours between additions; the alkaline solution used to maintain pH stability is a 0.5M NaOH solution.

[0014] Preferably, in step S5, the alcohol precipitation is performed by adding 3 times the volume of 95% ethanol to the supernatant and letting it stand for 12 h; the alternating use of different concentrations of ethanol for washing refers to washing the precipitate three times each with 95% ethanol and 70% ethanol; the dialysis is performed using a dialysis bag with a molecular weight cutoff of 3.5 kDa and dialysis in pure water at 4°C for 72 h.

[0015] This invention further claims a pectin-ellagic acid covalent complex, which is prepared using the same method for preparing pectin-ellagic acid covalent complexes, and which exhibits characteristic UV absorption peaks at 255 nm and 366 nm. 1 The 1H NMR spectrum shows an aromatic proton signal at 7.37 ppm.

[0016] The present invention further claims the use of the pectin-ellagic acid covalent complex in the preparation of emulsions, the emulsions comprising the pectin-ellagic acid covalent complex and an oil phase; the oil phase being olive oil or medium-chain triglycerides.

[0017] Preferably, the preparation method of the emulsion includes: dissolving the pectin-ellagic acid covalent complex in a citrate-phosphate buffer solution at pH 4.5 to prepare a complex solution of 2-10 mg / mL; mixing the complex solution with the oil phase at a volume ratio of 9:1; subjecting the mixture to high-speed shearing at 12000-15000 rpm for 3 min to obtain a crude emulsion; and then subjecting the mixture to ultrasonic treatment at 200-600W for 8-12 min to obtain a stable, oil-in-water emulsion.

[0018] The present invention has at least the following beneficial effects: Firstly, this invention constructs a water-in-oil microemulsion dispersion system with a specific volume ratio and combines it with a stepwise enzymatic grafting strategy to highly disperse insoluble ellagic acid in the pectin aqueous phase as nano-sized droplets. At the same time, it provides a huge oil-water interface for lipase to activate its interfacial catalytic activity, thereby solving the contradiction between fully dissolving the substrate and maintaining enzyme activity. Moreover, it does not require high-concentration organic solvents, has mild reaction conditions, high grafting efficiency, and a green and safe process. Secondly, this invention utilizes lipase catalysis to achieve directional covalent grafting of ellagic acid onto pectin. The aromatic hydrophobic structure of ellagic acid, as a hydrophobic anchor point, is introduced into the pectin molecular chain, significantly regulating the hydrophilic / hydrophobic balance of pectin and enhancing its surface amphiphilicity. This greatly improves the migration, adsorption, diffusion, and rearrangement capabilities of pectin at the oil-water interface, while effectively increasing the water contact angle, reducing the dynamic interfacial tension, and endowing the modified pectin with excellent emulsifying activity and interfacial stability. Thirdly, the pectin-ellagic acid covalent complex obtained in this invention is prepared using naturally sourced pectin and ellagic acid through a mild and efficient enzymatic grafting process. It is highly safe and fully preserves the pectin backbone structure. The pectin-ellagic acid covalent complex can form a stable emulsion system with fine and uniform particle size, high absolute value of ζ-potential, and significantly enhanced electrostatic repulsion and steric hindrance effects between droplets. It has outstanding physical and storage stability and has broad industrial application prospects in the fields of functional food ingredients and natural emulsifiers. Fourth, this invention introduces trace amounts of hydrophobically modified silica nanoparticles as an interface stabilizer into the microemulsion system. Combined with intermittent high-speed shearing treatment during the reaction process, the synergistic effect of irreversible interfacial adsorption and periodic forced dispersion of nanoparticles effectively inhibits the aggregation and Ostwald ripening of microemulsion droplets during the stirring reaction process of up to 30-40 hours, significantly improving the long-term dynamic stability of the microemulsion system and the probability of continuous and effective contact between enzyme and substrate. Fifth, the pectin-ellagic acid covalent complex prepared by this invention exhibits characteristic signals confirming covalent bonding in ultraviolet spectroscopy and proton nuclear magnetic resonance spectroscopy, with a clear structure. The pectin-ellagic acid covalent complex combines the emulsifying and stabilizing function of pectin with the antioxidant activity of ellagic acid. It can form a highly stable oil-in-water emulsion with olive oil or medium-chain triglycerides through a simple shear-ultrasound two-step emulsification method, providing an ideal new multifunctional emulsifying material for functional food ingredients, active substance delivery carriers, and other fields.

[0019] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Attached Figure Description

[0020] Figure 1 The UV absorption spectra of the citrus pectin-ellagic acid covalent complexes of the present invention at different mass ratios are shown. Figure 2 The UV absorption spectra of apple pectin-ellagic acid covalent complexes with different mass ratios according to the present invention are shown. Figure 3 A bar chart showing the grafting degree of ellagic acid in pectin-ellagic acid covalent complexes of different mass ratios according to the present invention; Figure 4 The above are the H NMR spectra of the citrus pectin-ellagic acid covalent complexes of different mass ratios of the present invention. Figure 5 The H NMR spectra of apple pectin-ellagic acid covalent complexes of different mass ratios in this invention are shown. Figure 6 This is a comparison chart of the DPPH free radical scavenging capabilities of pectin-ellagic acid covalent complexes with different mass ratios in this invention. Figure 7 This is a comparison chart of the ABTS free radical scavenging capabilities of pectin-ellagic acid covalent complexes with different mass ratios in this invention. Figure 8 This is a comparison chart of the iron ion reducing power of pectin-ellagic acid covalent complexes with different mass ratios according to the present invention; Figure 9 This is a comparison of the physical samples of pectin-ellagic acid covalent complex emulsions of different mass ratios after 72 hours of storage according to the present invention. Figure 10 This is a comparison chart of the emulsifying properties of pectin-ellagic acid covalent complex emulsions with different mass ratios according to the present invention; Figure 11 Laser confocal microscopy images of citrus pectin-ellagic acid covalent complex emulsions with different mass ratios according to the present invention; Figure 12 Laser confocal microscopy images of apple pectin-ellagic acid covalent complex emulsions with different mass ratios according to the present invention. Detailed Implementation

[0022] The present invention will now be described in further detail with reference to the accompanying drawings, so that those skilled in the art can implement it based on the description.

[0023] It should be understood that terms such as “having,” “comprising,” and “including” as used herein do not exclude the presence or addition of one or more other elements or combinations thereof.

[0024] Example 1: Preparation of Citrus Pectin-Ellagic Acid Covalent Complex (CP-EA) S1. Constructing the aqueous phase: Dissolve 10g of citrus pectin (CP) in 500mL of phosphate buffer solution with a pH of 7.5 to obtain a pectin solution; S2. Construction of organic phases: 1g, 2.5g and 5g of ellagic acid were dissolved in 100mL of dimethyl sulfoxide, sonicated for 10min and then 400mL of tetrahydrofuran were added to obtain organic solutions of ellagic acid of different concentrations. S3. Preparation of microemulsion system: Under high-speed shearing conditions of 8000 rpm, the ellagic acid organic solutions of different solubilities obtained in step S2 were slowly added to the pectin solution in step S1, and the high-speed shearing was carried out for 45 seconds to form an oil-in-water microemulsion dispersion. S4. Stepwise enzymatic grafting: Lipase derived from Aspergillus oryzae with an activity of 300,000 U / g was added to the microemulsion dispersion of step S3 in two equal portions, with a total lipase amount of 0.3g. The reaction was carried out at 50℃ and pH 7.2±0.1 for 36h with stirring. During the reaction, the pH value was measured every 12h and 0.5M NaOH solution was added dropwise to maintain the pH stable at 7.2. S5. After the reaction in step S4 is completed, the tetrahydrofuran is removed by rotary evaporation. The mixture is then centrifuged at 10,000 rpm for 30 min to remove lipase and unreacted ellagic acid. The supernatant is collected, and ethanol (3 times its volume) is added to the supernatant for precipitation. After standing for 12 h, the precipitate is collected and washed three times each with 95% and 70% ethanol to remove residual small molecule impurities. The precipitate is redissolved in 500 mL of ultrapure water and centrifuged at 10,000 rpm for 30 min. The supernatant is collected and placed in a 3.5 kDa dialysis bag, and dialyzed at 4 ℃ for 72 h to obtain a purified solution. The purified solution is freeze-dried to obtain the citrus pectin-ellagic acid covalent complex. In the pectin-ellagic acid covalent complex, the mass ratio of pectin to ellagic acid is 10:1, 4:1, or 2:1.

[0025] The obtained citrus pectin-ellagic acid covalent complex was prepared into a 1.0% (w / w) solution, completely dissolved in a pH 4.5 citrate-phosphate buffer, mixed with 10% (v:v) olive oil, and sheared at 15000 rpm for 3 min to obtain a crude emulsion. The emulsion was then sonicated at 400 W for 10 min to obtain an emulsion.

[0026] Example 2: Preparation of apple pectin-ellagic acid covalent complex (AP-EA) Except for replacing 10g of citrus pectin (CP) in the raw materials with 10g of apple pectin (AP), all other steps were the same as in Example 1, resulting in an apple pectin-ellagic acid covalent complex and the corresponding emulsion.

[0027] The pectin-ellagic acid covalent complexes with different mass ratios obtained in Examples 1 and 2 were subjected to ultraviolet absorption spectroscopy analysis. The experimental method is as follows: the pectin-ellagic acid covalent complexes with different mass ratios were dissolved in ultrapure water to prepare sample solutions of 1 mg / mL. The ultraviolet absorption spectra were scanned in the range of 200-450 nm using an ultraviolet spectrophotometer, and the ultraviolet absorption spectra were recorded. The ultraviolet absorption spectra of the citrus pectin-ellagic acid covalent complexes are shown in the figure below. Figure 1 The UV absorption spectra of the apple pectin-ellagic acid covalent complex are shown in [the table below]. Figure 2 .

[0028] Figure 1 and Figure 2The results showed that ungrafted natural pectin exhibited smooth absorption curves in the UV and visible light regions of 250 nm to 450 nm, without obvious characteristic absorption peaks. After the grafting reaction, the pectin-ellagic acid covalent complex showed obvious absorption peaks in the 230–300 nm and 320–380 nm regions, with a distinct absorption shoulder in the 250–280 nm range and a broadened absorption band near 350–370 nm, indicating that the aromatic chromophore of ellagic acid had been successfully introduced into the pectin system. Furthermore, the spectral curves for different composite ratios showed a strong concentration dependence. With increasing ellagic acid content, the absorbance of the pectin-ellagic acid covalent complex at 255 nm and 365 nm showed a regular gradient increase. This trend also reflects a positive correlation between the grafting rate or loading rate of the complex and the substrate concentration; higher substrate concentrations in the enzymatic system drive a positive shift in reaction equilibrium, prompting more ellagic acid groups to bind to the pectin backbone.

[0029] Grafting degree analysis was performed on the pectin-ellagic acid covalent complexes with different mass ratios obtained in Examples 1 and 2. The experimental method is as follows: The grafting degree was determined by the Folin-Ciocalteu method. 1 mL of a 5 mg / mL pectin-ellagic acid covalent complex solution was taken, and 2.5 mL of 10% Folin-Ciocalteu reagent was added. After reacting in the dark for 5 min, 2 mL of 7.5% Na₂CO₃ solution was added, and the reaction was continued in the dark for 1 h. The absorbance was measured at 765 nm, and the grafting degree was calculated according to the standard curve. The results are expressed as mg EA / g sample. Figure 3 As shown.

[0030] like Figure 3 The grafting degree of the complex also exhibits a high dependence on the concentration of the reaction substrate. Specifically, the grafting amount in the CP-EA system significantly increased from 2.48 mg EA / g to approximately 5.86 mg EA / g; while the grafting amount in the AP-EA system increased from 3.65 mg EA / g to 7.94 mg EA / g, indicating that the method of this invention can effectively achieve covalent grafting of ellagic acid onto pectin. Furthermore, this typical dose-dependent kinetic behavior further confirms the catalytic mechanism of lipase in the water / organic biphase system. Higher concentrations of EA significantly increase the substrate chemical potential in the organic phase, thereby greatly promoting the forward shift of the thermodynamic esterification and transesterification equilibrium, effectively overcoming the steric hindrance effect between pectin polymer chains, and achieving high-density covalent loading of polyphenolic groups.

[0031] The pectin-ellagic acid covalent complexes obtained in Examples 1 and 2 at different mass ratios were subjected to... 1The 1H NMR analysis was performed as follows: 10 mg of sample was accurately weighed and dissolved in 1 mL of D₂O. The concentration was recorded using a 600 MHz NMR spectrometer at 25 °C. 1 1H NMR spectrum, citrus pectin-ellagic acid covalent complex 1 H NMR spectrum as follows Figure 4 Apple pectin-ellagic acid covalent complex 1 H NMR spectrum as follows Figure 5 .

[0032] like Figure 4 and Figure 5 As shown, natural pectin exhibits typical pectin glycocycle proton signals in the 3.0–5.5 ppm region. The signals near 5.0–5.3 ppm can be attributed to anomeric proton signals from galacturonic acid residues, while the 3.6–4.5 ppm region mainly corresponds to glycocycle protons such as H2, H3, and H4 from GalA residues. The 3.7–8 ppm region shows a methoxyl signal. Compared to natural pectin, the grafted sample, while retaining the aforementioned characteristic pectin signals, shows a new aromatic region signal near 7.37 ppm. This signal is clearly attributed to the highly conjugated aromatic ring protons (H4 / H9) on the grafted ellagic acid molecule, indicating that this invention has successfully introduced ellagic acid into the pectin molecule. Because ellagic acid is covalently grafted into the pectin polymer network, its molecular thermal motion is strongly spatially confined by the polysaccharide chains and affected by the electron cloud deshielding effect of newly formed ester bonds. Therefore, the chemical shift of its aromatic protons exhibits a certain degree of shift and peak broadening compared to the free state. Therefore, the overall preservation and slight shift of the signals in the sugar ring and methoxy regions in this study indicate that the composite post-gum backbone still exists, while the introduction of ellagic acid significantly alters the chemical environment around the GalA residues.

[0033] The antioxidant properties of pectin-ellagic acid covalent complexes with different mass ratios obtained in Examples 1 and 2 were analyzed using the following methods: The antioxidant properties of the samples were determined using DPPH free radical scavenging ability, ABTS free radical scavenging ability, and ferric ion reducing ability (FRAP). For DPPH determination, a 0.1% (w / v) sample solution and a 0.2 mM DPPH methanol solution were prepared, and the absorbance at 517 nm was approximately 0.9. 900 μL of DPPH solution was mixed with 100 μL of sample solution, and the mixture was reacted at 25 °C in the dark for 1 h. The absorbance was then measured at 517 nm. The results are shown below. Figure 6For ABTS determination, 7 mM ABTS stock solution was mixed with an equal volume of 2.45 mM K₂S₂O₈ solution and reacted in the dark for 12–16 h. Before use, it was diluted 20-fold to achieve an absorbance of approximately 0.9 at 734 nm. 900 μL of ABTS working solution was mixed with 100 μL of sample solution and reacted at 25 °C in the dark for 6 min. The absorbance was then measured at 734 nm. The results are as follows: Figure 7 For FRAP determination, the sample solution was mixed with FeCl3, acetate-sodium acetate buffer, and TPTZ working solution, and incubated at 37 °C in the dark for 2 h. The absorbance was then measured at 593 nm. A standard curve was prepared using vitamin C solutions with concentrations ranging from 0–300 μmol / L. Results are expressed as vitamin C equivalents, as shown below. Figure 8 .

[0034] like Figures 6-8 Both CP and AP exhibited extremely weak activity in the three antioxidant systems. This is because the macromolecular backbone of natural pectin is mainly composed of galacturonic acid and neutral sugar residues, lacking conjugated active groups that can effectively donate hydrogen protons or single electrons to quench free radicals and reduce metal ions. However, after grafting with ellagic acid, the three antioxidant indicators of the complex were significantly increased, and overall, the enhancement increased with the increase of the ellagic acid ratio, showing a trend of 2:1>4:1>10:1>protopectin. Therefore, the introduction of ellagic acid significantly enhanced the free radical scavenging and reducing abilities of the pectin system, and the antioxidant enhancement effect was closely related to the ellagic acid ratio.

[0035] like Figure 6 and Figure 7 The DPPH and ABTS free radical scavenging abilities and FRAP of the citrus pectin-ellagic acid covalent complex and the apple pectin-ellagic acid covalent complex were significantly improved, indicating that the composite samples not only have stronger free radical scavenging effects but also significantly improved electron transfer capabilities. This phenomenon is closely related to the structural characteristics of ellagic acid. Ellagic acid is a typical polyphenol containing multiple phenolic hydroxyl groups and conjugated aromatic structures, possessing strong hydrogen and electron donor capabilities. It has shown significant activity in various in vitro antioxidant models, including DPPH, ABTS, and Fe³⁺ reduction. Therefore, grafting ellagic acid simultaneously improves the antioxidant properties of pectin.

[0036] Emulsions prepared from pectin-ellagic acid covalent complexes with different mass ratios obtained in Examples 1 and 2 were analyzed for emulsification performance. The experimental method was as follows: A 1.0% (w / v) solution of the pectin-ellagic acid covalent complex was prepared in a citrate-phosphate buffer solution at pH 4.5. The sample solution was then mixed with 10% (v:v) olive oil and homogenized at 15,000 rpm for 3 min using a high-speed homogenizer to obtain a crude emulsion. The emulsion was then sonicated at 400 W for 10 min to obtain a fresh emulsion. The emulsification performance was evaluated using the Emulsification Activity Index (EAI) and the Emulsification Stability Index (ESI).

[0037] Prepare a 0.1% (w / w) sodium dodecyl sulfate (SDS) aqueous solution. Add 40 μL of fresh emulsion to 10 mL of SDS solution, mix thoroughly, and measure the absorbance (A0) at 500 nm. After allowing the emulsion to stand for 10 min, add 40 μL of the emulsion to 10 mL of SDS solution and measure the absorbance (A0) at 500 nm. 10 ).

[0038] (1) (2) Where DF is the dilution factor, C is the pectin concentration before emulsion formation (g / mL), θ is the optical path length (0.01), Φ is the oil volume fraction, A0 is the absorbance of the fresh emulsion, and A 10 It is the absorbance of the emulsion after standing for 10 minutes.

[0039] The macroscopic appearance changes of emulsions are the most intuitive means of assessing their physical stability. Emulsions prepared from citrus pectin-ellagic acid covalent complexes and apple pectin-ellagic acid covalent complexes show the following appearances: Figure 9 As shown, the emulsifying activity index (EAI) of emulsions prepared from citrus pectin-ellagic acid covalent complexes and emulsions prepared from apple pectin-ellagic acid covalent complexes is as follows: Figure 10 As shown.

[0040] like Figure 9All fresh emulsions exhibited a uniform, dense, milky-white appearance with no visible phase separation. This indicates that under the synergistic effect of high-speed shearing and ultrasonic cavitation, all samples effectively encapsulated oil droplets and formed an oil-in-water (O / W) coarse dispersion system. After 24 hours of storage, significant differences began to appear between the different systems. Aqueous phase precipitation appeared at the bottom of all samples, with CP-EA (10:1) and CP-EA (4:1) showing the most significant precipitation. In addition, a shallower lipid layer formed on top of natural pectin AP and CP, indicating that phase separation had occurred to some extent. After 72 hours of continued storage, all samples showed varying degrees of stratification, floating, or bottom precipitation of aqueous phase, but the degree of stratification differed significantly. Overall, it was observed that a relatively obvious aqueous phase layer appeared at the bottom of the CP and AP emulsions, while a lipid layer appeared at the top, indicating that CP and AP had weak resistance to oil droplet floating and flocculation, and were unable to maintain a completely homogeneous state during storage. The macroscopic stability of the composite samples was influenced by both the pectin source and the ellagic acid feed ratio. As the grafting ratio of ellagic acid in the composite increased, the phase separation of the emulsion was significantly reduced. In particular, the AP-EA (4:1) and AP-EA (2:1) groups showed only a very small amount of aqueous phase at the bottom after 72 h, and the overall emulsion remained highly uniform, indicating that ellagic acid grafting can effectively improve the storage stability of pectin emulsions.

[0041] like Figure 10 The emulsifying activity index (EAI) of CP and AP were approximately 12.1 m² / g and 12.4 m² / g, respectively, indicating that both pectins possess a certain emulsifying ability. This is because the natural pectin backbone contains a large amount of hydrophilic galacturonic acid and neutral sugars, resulting in low surface activity and difficulty in rapid and spontaneous adsorption at the oil-water interface. After EA grafting, the overall EAI of the covalent complex increased. For the CP system, CP-EA (10:1) showed no significant change, while CP-EA (4:1) and CP-EA (2:1) reached as high as 19.1 m² / g. 2 / g and 22.2 m 2 / g, indicating that a medium-to-high feed ratio can significantly improve the emulsifying activity of citrus pectin. For the AP system, the EAI increased from 12.4 m... 2 / g gradually increased to 23.4, 25.5 and 27.3 m 2 The percentage of pectin molecules grafted with ellagic acid (EAI) showed a significant upward trend. This indicates that grafting with ellagic acid significantly improved the interfacial activity of pectin molecules, thereby increasing the EAI. Simultaneously, the abundant phenolic hydroxyl groups and aromatic conjugated skeleton in the ellagic acid molecule can enhance the interaction between pectin chains through hydrogen bonding, and also increase the hydrophobicity of the system. This enhancement of amphiphilicity significantly reduces the interfacial free energy, greatly increasing the diffusion and adsorption rate of the polymer to the oil-water interface. Therefore, under the same homogeneous energy consumption, it can effectively stabilize smaller and more numerous oil droplets, generating a larger specific surface area.

[0042] Emulsions prepared from pectin-ellagic acid covalent complexes with different mass ratios obtained in Examples 1 and 2 were analyzed by laser confocal microscopy. The experimental method was as follows: 100 μL of emulsion was placed in a centrifuge tube, and equal volumes of Nile Red and Nile Blue staining solutions were added sequentially. After thorough vortexing and mixing, the mixture was allowed to stand for 1 h in the dark. The concentrations of Nile Red and Nile Blue staining solutions were both 0.1 wt%, prepared using 1,2-propanediol and ultrapure water, respectively. Approximately 10 μL of the stained emulsion was placed on a glass slide, covered with a coverslip, and observed using a laser confocal microscope. The excitation wavelengths were 488 nm and 633 nm, respectively, and images were acquired at 40x magnification. The laser confocal microscopy images further revealed the spatial distribution characteristics of the oil phase and the complex in the emulsion. The laser confocal microscopy images of the emulsions prepared from citrus pectin-ellagic acid covalent complexes and apple pectin-ellagic acid covalent complexes are shown below. Figure 11 and Figure 12 .

[0043] like Figures 11-12 In the Nile Red staining images, the red signals mainly correspond to the distribution of oil droplets, while the Nile Blue staining images reflect the distribution of the complex in the continuous phase and near the interface. The orange-yellow areas in the overlay images can be used to characterize the degree of co-localization between the complex and the oil droplet interface. The oil droplets in the CP and AP emulsions are large in size and unevenly distributed, with local aggregation, indicating that the unmodified pectin has limited ability to cover the newly formed oil droplet interface. In contrast, after covalent grafting with EA, the oil droplets in each group of emulsions are significantly refined and more dispersed. Furthermore, as the proportion of EA increases, the droplet size gradually decreases and the distribution becomes more uniform, especially in the CP-EA (4:1), CP-EA (2:1), AP-EA (4:1), and AP-EA (2:1) groups, which exhibit even finer and more uniform droplet structures. The interface co-localization signal in the overlay images is more continuous, indicating that the pectin-ellagic acid covalent complex can more effectively adsorb and cover the oil droplet surface, forming a more complete interface layer, thereby inhibiting the re-agglomeration of droplets after homogenization and ultrasonic treatment. The results indicate that EA grafting enhances the amphiphilicity and interfacial coverage efficiency of pectin, resulting in better microscopic uniformity and short-term dispersion stability of the emulsion.

[0044] Example 3 Except for step S3, in which 0.5% of the pectin mass of hydrophobic modified silica nanoparticles are added to the reaction system of ellagic acid organic solution and pectin solution before high-speed shearing, the rest is the same as in Example 1. The hydrophobic modified silica nanoparticles are removed in the subsequent centrifugation operation to obtain citrus pectin-ellagic acid covalent complex and corresponding emulsion.

[0045] The particle size and distribution of the citrus pectin-ellagic acid covalent complex microemulsions obtained in Examples 1 and 3 were measured at 0h, 12h, 24h, and 36h after the start of the reaction using dynamic light scattering. The microemulsions obtained in Example 3 showed smaller droplet size, narrower distribution, and significantly lower aggregation than those obtained in Example 1. The zeta potential of the microemulsions obtained in Examples 1 and 3 was measured using electrophoresis. The microemulsions obtained in Example 3 showed a higher absolute value of zeta potential and enhanced electrostatic stability. The microemulsions of Examples 1 and 3 were observed and recorded after static observation. 3. The time it takes for the aqueous and oil phases of the obtained citrus pectin-ellagic acid covalent complex microemulsion system to show visible separation was measured. In Example 3, the citrus pectin-ellagic acid covalent complex microemulsion droplet showed no visible stratification within 24-36 hours. The grafting degree of ellagic acid in the citrus pectin-ellagic acid covalent complexes obtained in Examples 1 and 3 was determined using the Folin-Ciocalteu method, with the specific method as described above. The grafting degree of ellagic acid in the citrus pectin-ellagic acid covalent complex obtained in Example 3 was 21.74% higher than that in Example 1. The turbidity of the supernatant after the reaction in Examples 1 and 3 was measured using a UV spectrophotometer at 500 nm. The absorbance was measured at a wavelength of nm. In Example 3, the turbidity was lower after the reaction, indicating that less unreacted ellagic acid precipitated. The residual amount of free ellagic acid in the final products of Examples 1 and 3 was quantitatively analyzed by high performance liquid chromatography. The content of free ellagic acid in the final product of Example 3 was significantly lower than that in the final product of Example 1.

[0046] Example 4 Except for the stirring reaction in step S4, where stirring was paused every 10 hours and then sheared at 8000 rpm for 10-20 seconds before stirring resumed, the rest of the process was the same as in Example 3. The hydrophobically modified silica nanoparticles were removed in the subsequent centrifugation operation to obtain the citrus pectin-ellagic acid covalent complex and the corresponding emulsion.

[0047] The grafting degree, EAI, and ESI of Examples 1, 3, and 4 were determined using the above method, and the results are shown in Table 1.

[0048] Table 1. Comprehensive evaluation index of citrus pectin-ellagic acid (10:1) covalent complex Table 1 shows that from Example 1 to Example 3 and then to Example 4, the three key performance indicators—grafting degree, emulsifying activity index (EAI), and emulsifying stability index (ESI)—all exhibit a progressively increasing trend. Specifically, Example 1's basic scheme achieved a lower grafting degree and emulsifying performance; Example 3, after introducing hydrophobically modified silica nanoparticles, showed a significant improvement in all three indicators; and Example 4, by further adding intermittent high-speed shearing treatment on top of the nanoparticles, achieved the highest levels for all three indicators. This monotonically increasing trend clearly reveals the positive effects of the two process improvements and their synergistic effect when combined.

[0049] Hydrophobically modified silica nanoparticles, acting as interfacial stabilizers, irreversibly adsorb onto the oil-water interface in the microemulsion system, significantly inhibiting droplet aggregation and Ostwald ripening during the 30-40 hour enzymatic reaction. This interfacial pinning effect maintains the high specific surface area and long-term dynamic stability of the oil-water interface, providing a continuously stable catalytic interface for lipases, while ensuring the nanoscale dispersion of poorly soluble ellagic acid in the organic phase. This significantly increases the effective collision frequency and esterification efficiency between ellagic acid and pectin molecules. Consequently, the grafting degree increases significantly from Example 1 to Example 3. Intermittent high-speed shearing treatment, by forcibly redispersing the reaction system at regular intervals, effectively overcomes problems such as localized droplet aggregation, interfacial film fatigue, and uneven reaction that may result from prolonged continuous stirring. This periodic external force input reactivates the homogeneity of the microemulsion system. Especially when synergistically combined with nanoparticles, the nanoparticles provide thermodynamic interfacial stability, while intermittent shearing provides kinetic continuous dispersion; together, they ensure efficient enzyme-substrate contact throughout the entire reaction cycle. Therefore, the grafting degree in Example 4 was further increased. The increase in grafting degree directly determines the amphiphilicity of the pectin-ellagic acid covalent complex. After ellagic acid, as a hydrophobic aromatic group, is covalently introduced into the hydrophilic skeleton of pectin, it significantly regulates the hydrophilic-hydrophobic balance of the molecule and enhances the adsorption, spreading, and rearrangement ability of pectin at the oil-water interface. Therefore, the emulsifying activity index (EAI) and the emulsifying stability index (ESI) increase simultaneously with the increase in grafting degree. A higher grafting degree means that more hydrophobic ellagic acid anchor points are introduced into the pectin molecular chain, which on the one hand reduces the oil-water interfacial tension, enabling the formation of smaller and more uniform oil droplets under the same homogenization energy consumption; on the other hand, it enhances the electrostatic repulsion and steric hindrance effect between droplets, effectively inhibiting the aggregation, stratification, or emulsification of the emulsion, thereby significantly improving the emulsifying stability.

[0050] This application achieves a significant leap in grafting efficiency and product performance at extremely low cost (micro-sized nanoparticles, simple periodic shearing operations) by synergistically employing two physical enhancement methods: nanoparticle interfacial stabilization and intermittent shearing dynamic dispersion. This is done without altering the enzyme's catalytic nature or mild reaction conditions. Compared to the basic scheme in Example 1, Example 4 shows several times, or even multiple times, improvements in grafting degree, EAI, and ESI. The process improvements of this invention are particularly suitable for the enzymatic grafting modification of ellagic acid and other sterically hindered, poorly soluble polyphenols, further providing a practical and feasible technical path for the green preparation of pectin-based high-efficiency emulsifying materials.

[0051] In summary, this invention utilizes lipase catalysis to covalently graft ellagic acid onto pectin, which significantly enhances the amphiphilicity, interfacial adsorption capacity, and emulsifying properties of pectin, while also imparting stronger antioxidant activity. The resulting complex can be used to prepare emulsion systems with smaller particle size, more uniform dispersion, and higher stability, thus showing promising application prospects in food emulsions, functional ingredients, and active delivery systems.

[0052] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.

Claims

1. A method for preparing a pectin-ellagic acid covalent complex, characterized in that, include: S1. Constructing the aqueous phase: Dissolve pectin in phosphate buffer to obtain a pectin solution; S2. Constructing the organic phase: Ellagic acid is dissolved in dimethyl sulfoxide, sonicated until completely dissolved, and then tetrahydrofuran is added to obtain an organic solution of ellagic acid. The volume ratio of dimethyl sulfoxide to tetrahydrofuran is 1:3 to 1:

5. S3. Preparation of microemulsion system: Under high-speed shearing conditions of 8000~10000rpm, the ellagic acid organic solution of step S2 is slowly added to the pectin solution of step S1, and the high-speed shearing is carried out for 40~50s to form an oil-in-water microemulsion dispersion. S4. Stepwise enzymatic grafting: Lipase with an activity of 300,000 U / g derived from Aspergillus oryzae was added to the microemulsion dispersion of step S3 in two portions. The mixture was stirred and reacted at 50°C and pH 7.2±0.1 for 30-40 hours. During the reaction, the pH value was measured at regular intervals and alkali solution was added dropwise to maintain pH stability. S5. After the reaction in step S4 is completed, remove the organic solvent, centrifuge to remove insoluble matter, and precipitate the supernatant with alcohol, wash with different concentrations of ethanol alternately, resolubilize, dialyze and freeze dry to obtain the pectin-ellagic acid covalent complex. The mass ratio of pectin, ellagic acid and lipase is 2~10:1~5:0.

3.

2. The method for preparing the pectin-ellagic acid covalent complex as described in claim 1, characterized in that, In step S3, 0.5-2% of hydrophobic modified silica nanoparticles by weight of pectin are added to the reaction system of high-speed shear-progressive ellagic acid organic solution and pectin solution.

3. The method for preparing the pectin-ellagic acid covalent complex as described in claim 2, characterized in that, During the stirring reaction in step S4, stirring is paused every 6 to 10 hours, and then sheared for 10 to 20 seconds under high-speed shearing conditions of 8000 to 10000 rpm before stirring is resumed.

4. The method for preparing the pectin-ellagic acid covalent complex as described in claim 3, characterized in that, The pectin is apple pectin or citrus pectin.

5. The method for preparing the pectin-ellagic acid covalent complex as described in claim 4, characterized in that, In step S1, the pH value of the phosphate buffer is 7.2~7.8, and the concentration of the pectin solution is 4~20 mg / mL; in step S2, the concentration of ellagic acid in the mixed organic solvent of dimethyl sulfoxide and tetrahydrofuran is 2~10 mg / mL.

6. The method for preparing the pectin-ellagic acid covalent complex as described in claim 5, characterized in that, In step S4, the lipase is added in two equal amounts, with an interval of 6-15 hours between additions; the alkaline solution used to maintain pH stability is a 0.5M NaOH solution.

7. The method for preparing the pectin-ellagic acid covalent complex as described in claim 6, characterized in that, In step S5, alcohol precipitation involves adding three times the volume of 95% ethanol to the supernatant and allowing it to stand for 12 hours; the alternating washing with different concentrations of ethanol refers to washing the precipitate three times each with 95% ethanol and 70% ethanol; the dialysis is performed using a dialysis bag with a molecular weight cutoff of 3.5 kDa and dialysis in pure water at 4°C for 72 hours.

8. A pectin-ellagic acid covalent complex, characterized in that, The pectin-ellagic acid covalent complex is prepared by the method described in any one of claims 1 to 7. The pectin-ellagic acid covalent complex exhibits characteristic ultraviolet absorption peaks at 255 nm and 366 nm. 1 The 1H NMR spectrum shows an aromatic proton signal at 7.37 ppm.

9. The application of the pectin-ellagic acid covalent complex as described in claim 8 in the preparation of emulsions, characterized in that, The emulsion comprises the pectin-ellagic acid covalent complex and an oil phase; the oil phase is olive oil or medium-chain triglycerides.

10. The application as described in claim 9, characterized in that, The preparation method of the emulsion includes: dissolving the pectin-ellagic acid covalent complex in a citrate-phosphate buffer solution at pH 4.5 to prepare a complex solution of 2-10 mg / mL; mixing the complex solution with the oil phase at a volume ratio of 9:1; and then subjecting the mixture to high-speed shearing at 12000-15000 rpm for 3 min to obtain a crude emulsion. Finally, the mixture is subjected to ultrasonic treatment at 200-600W for 8-12 min to obtain a stable, oil-in-water emulsion.

Citation Information

Patent Citations

  • Pectin graft copolymer as well as preparation method and application thereof

    CN113072662A

  • Pectin graft copolymer as well as preparation method and application thereof

    CN118048414A